2014
DOI: 10.1038/ajg.2013.278
|View full text |Cite
|
Sign up to set email alerts
|

Interview From Anywhere: Feasibility and Utility of Web-Based Videoconference Interviews in the Gastroenterology Fellowship Selection Process

Abstract: WVC can be an effective and useful tool in the fellowship interview process. It affords candidates increased flexibility, cost saving, convenience, and provides an option for participating in the selection process at more programs. For the programs and faculty, WVC has a potential to be an effective screening tool, can help minimize loss of clinical revenue and can also be an acceptable alternative to in-person interviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
138
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(144 citation statements)
references
References 5 publications
6
138
0
Order By: Relevance
“…Videoconferencing software applications have been used to conduct residency interviews in other medical specialties, generally in conjunction with a face-to-face interview on the same day or on a day shortly after the web-based interview. 5 , 8 - 10 The impact of web-based interviews on residency program admission results is unclear. A 2014 NRMP survey of US anesthesiology residency program directors cited interactions with faculty during interview and visit, interpersonal skills, and interactions with current residents during interview and visit as the three top factors determining an applicant's position on the residency program rank-order list.…”
Section: Introductionmentioning
confidence: 99%
“…Videoconferencing software applications have been used to conduct residency interviews in other medical specialties, generally in conjunction with a face-to-face interview on the same day or on a day shortly after the web-based interview. 5 , 8 - 10 The impact of web-based interviews on residency program admission results is unclear. A 2014 NRMP survey of US anesthesiology residency program directors cited interactions with faculty during interview and visit, interpersonal skills, and interactions with current residents during interview and visit as the three top factors determining an applicant's position on the residency program rank-order list.…”
Section: Introductionmentioning
confidence: 99%
“…Winter Storm Jonas was the impetus for the use of FaceTime interviews at the WVU SOM, and the interview process was successful for medical school recruiting. Although not previously reported for medical school recruiting, the use of digital interviewing has already been reported to be successful in the recruiting of residents and/or fellows in the fields of Pediatrics, Family Medicine, Anesthesiology, Urology and Gastroenterology (Nield et al, 2013;Edje et al, 2013;Vadi et al, 2016;Shah et al, 2012;Daram et al, 2014). We believe this is the first case study report about the successful use of FaceTime interviewing at the medical school level, and it may encourage admissions officials to expand the use of this modality in recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a gastroenterology fellowship program compared face-to-face interviews with WBVC and found that 81% of candidates stated that their WBVC experience met or exceeded their expectations, while 87% stated that it should be an option in fellowship interviews. 2 Another study estimated that WBVC interviews saved applicants anywhere from $349 to $784 and saved the program $586 per applicant. 3 Furthermore, a study that randomized applicants to Skype versus traditional on-site interviews showed that applicants and faculty favored using WBVC as an adjunct to on-site interviews and that applicants required significantly less time away from medical school when WBVCs were used.…”
Section: Videoconferencing Interviewsmentioning
confidence: 99%